PENGARUH STANDARD PRODUCT, QUALITY ASSURANCE, COMPETITIVE PRICE DAN DELIVERY ON TIME TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PRODUK BETON PRACETAK (STUDI KASUS DI PT. TJAKRINDO MAS – GRESIK ) - Chandra Kartika (Universitas Trunojoyo Madura, 2016)
This study aims to provide answers to most of its customers on issues concerning the relationship Standard Product, Quality Assurance, Competitive Deliverity On Time, On Time Delivery and given to the customer's manufacturing company in Gresik, because by observation and measurement beyond the more value-value which fell on the dimensions of Quality of Products at the Company's manufacturing Gresik, the more a complaint arising from the customer relationship product quality and quality asurance and competitive price and delivery of products supplied to the customer, so that the level of satisfaction and loyalty pelangganpun influence, and therefore researchers will examine the issue very krausal to increase the level of relationship satisfaction and loyalty in a manufacturing company, especially customers in manufacturing each and will test Model linkage of demensi Product, Quality Assurance, Competitive Deliverity On Time, And Delivery On Time to customer satisfaction and loyalty, First to determine the dimensions of the relationship marketing with mengkomper the existing situation in the company is manufacturing so as to improve its quality by way of the formation of a character customer to feel a service, the development of information systems related to marketing, education to corporate customers on product quality and Quality Assurance, Competitive Deliverity On Time And On Time Delivery in the company. and collect primary and secondary data through observation, surveys, questionnaires. Second to provide a refinement of the concept of dimensional analysis with regard to product quality and Quality Assurance, Competitive Deliverity On Time And On Time Delivery, with an increase in marketing services and marketing model building as well as provide an improved dimensional marketing. Implementation of the method applied is to use the sample size in this study were 100 respondents drawn from the customers who had come in the company to the place specified in the research study, namely in Gresik Manufacturing Company. This study used quantitative analysis through the method of analysis approaches explanatory or descriptive research, statistical path analysis, multiple linear regression and using the software SPSS for Windows 20.0, and IBM amous of an invention is expected to find a positive outcome and can describe the level of product quality better and certainty of variables Product, Quality Assurance, Competitive Deliverity On Time, On Time Delivery and clear in order to help improve the level of customer satisfaction and loyalty company's manufacturing in PT. Tjakrindo Mas Gresik.